2017
DOI: 10.3802/jgo.2017.28.e35
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of breast cancer in women with uterine myoma: a nationwide, population-based, case-control study

Abstract: ObjectiveTo evaluate if uterine myoma is associated with breast cancer.MethodsThis case-control study used a nationwide database in Taiwan. We identified 24,315 patients with newly diagnosed breast cancer as cases and matched them with 24,281 patients without breast cancer on age, sex, urbanization, income, and initial diagnosis date. Patients with prior mastectomy were excluded. We used logistic regression analysis to assess the association between uterine myoma and breast cancer while adjusting for confounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The mutation status can inform them on whether they should operate on suspicious adnexal masses [8]. Breast cancer patients are at high risk for uterine myoma [3]. In our study, we found 5 adnexal masses and 6 uterine myoma patients.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The mutation status can inform them on whether they should operate on suspicious adnexal masses [8]. Breast cancer patients are at high risk for uterine myoma [3]. In our study, we found 5 adnexal masses and 6 uterine myoma patients.…”
Section: Discussionmentioning
confidence: 50%
“…Gynecologic and gynecologic oncology clinic visits and consultations related to breast cancer diagnosis and treatment are performed for many reasons, including common gynecologic problems presenting with dysmenorrhea, menstrual irregularity with or without uterine myoma, adnexal masses, infertility, menopausal symptoms, bone loss related to use of GnRH agonist, and endometrial cancer risk evaluation associated with tamoxifen use [3][4][5][6][7][8]. BRCA mutation patients have a lifetime risk of breast and ovary cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study by Wise et al, in the USA, failed to find any association between the history of UL diagnosis and the overall incidence of breast cancer [ 5 ]. Two Asian studies based in Taiwan showed a higher incidence of breast cancer in patients with UL without increased mortality [ 6 - 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary exposure of interest in this study was uterine myoma, which was defined as women with a previous diagnosis of uterine myoma (ICD-9-CM 218 or 219.9) with at least three outpatient visits or one hospitalization within the year preceding the index date to increase the diagnosis accuracy. This method has been applied by our group in a previous study on uterine myoma [15]. Uterine myoma was diagnosed based on the patient's medical history, clinical features, bimanual palpation, and ultrasonography.…”
Section: Methodsmentioning
confidence: 99%